Modified V-Groove Slot Waveguide for DNA Hybridization Detection - Eman ELDamarawy; Ahmed M. Heikal; Salah S. A. Obayya; Mohamed Farhat O. Hameed (Applied Computational Electromagnetics Society Journal (ACES), 2020)
Highly sensitive slot waveguides are introduced and studied for DNA hybridization detection. In this investigation, two different configurations based on V-groove silicon on insulator (SOI) waveguides are analyzed using full vectorial finite element method. The suggested designs rely on improving the light confinement through the slot region at an operating wavelength of 1.55 μm. The power confinement, power density (PD), and effective index of the supported modes are studied for the conventional rectangular slot waveguide and proposed designs. Further, the effect of adding a plasmonic layer to the reported slot waveguides is implemented. It has been shown that the plasmonic layer increases the light confinement in the slot region with high potential for DNA hybridization detection with good confinement through the slot region.